2019
DOI: 10.1371/journal.pbio.3000549
|View full text |Cite
|
Sign up to set email alerts
|

A generic cell surface ligand system for studying cell–cell recognition

Abstract: Dose-response experiments are a mainstay of receptor biology studies and can reveal valuable insights into receptor function. Such studies of receptors that bind cell surface ligands are currently limited by the difficulty in manipulating the surface density of ligands at a cell–cell interface. Here, we describe a generic cell surface ligand system that allows precise manipulation of cell surface ligand densities over several orders of magnitude. These densities are robustly quantifiable, a major advance over … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 55 publications
0
17
0
Order By: Relevance
“…We have analyzed the level of uptake of TLRn lig -Pp3 on monocyte-derived DCs (moDCs), using 10 nM of TLR4 lig -Pp3 ( 1 ) or TLR7 lig -Pp3 ( 2 ), both labeled with Alexa fluor 647, by flow cytometry and confocal microscopy (CM) . Flow cytometry measurements indicated that TLRn lig -Pp3 were uptaken by moDCs in a time-dependent manner, which is faster and higher for TLR4 lig -Pp3 compared to TLR7 lig -Pp3 (Figure A).…”
Section: Resultsmentioning
confidence: 99%
“…We have analyzed the level of uptake of TLRn lig -Pp3 on monocyte-derived DCs (moDCs), using 10 nM of TLR4 lig -Pp3 ( 1 ) or TLR7 lig -Pp3 ( 2 ), both labeled with Alexa fluor 647, by flow cytometry and confocal microscopy (CM) . Flow cytometry measurements indicated that TLRn lig -Pp3 were uptaken by moDCs in a time-dependent manner, which is faster and higher for TLR4 lig -Pp3 compared to TLR7 lig -Pp3 (Figure A).…”
Section: Resultsmentioning
confidence: 99%
“…As previously, we used a human Jurkat T-cell line expressing the 1G4 TCR [ 27 ]. As this line does not express CD8 (CD8−), we used lentiviral transduction [ 28 ] to produce a version that expresses CD8αβ (CD8+). Cell receptor expression was checked with flow cytometry, using a LSRFortessa X20 flow cytometer (Beckton-Dickinson, Franklin Lakes, NJ, USA).…”
Section: Methodsmentioning
confidence: 99%
“…5C). 85 Target cells expressed a surface protein bearing a twin Strep-tag. Then, questions about cell-cell interactions in terms of ligand length, valency and affinity could be addressed in a modular fashion (without making a huge range of stably transfected cell clones), through titrating in a bridging molecule of SpyCatcher linked to Strep-Tactin (Fig.…”
Section: Cellular Applicationsmentioning
confidence: 99%
“…5C). 85 Membrane decoration may also be applied for vaccine assembly: Outer Membrane Vesicles (OMVs) from attenuated Salmonella displaying a SpyTag-linked E. coli autotransporter facilitate display of SpyCatcher-linked immunogens (Fig. 5D).…”
Section: Cellular Applicationsmentioning
confidence: 99%